EDUKASI PERILAKU PREVENTIF MASYARAKAT MELALUI VIDEO IKLAN “PANGGILAN 110 PELAYANAN PUBLIK TERPADU” DI KOTA BATAM - Evaliata Br Sembiring; Azhari Muda Tanjung (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2022)
One form of service provided by the Riau Islands Regional Police during the Covid-19 pandemic is an emergency call service through the call for 110 integrated public services. To counter the public perception that dealing with the police is tedious and complicated, it is necessary to have media to facilitate the public in reporting disruptions to law and order. One of the media that can be used is video to educate, socialize or inform its services. The research begins with making public service advertisements about 110 in the form of video. Analysis of the effect of the resulting video on people's behavior was then carried out. The research method used was Research and Development, namely making videos, applying the stages of making multimedia products to Luther Sutopo, and analyzing the effect of video on people's behavior on reporting through 110. After the video has been made and has gone through the testing process, it is then analyzed based on the results of observations by reviewers in alpha testing and beta testing using T-test. The result of the research is a video advertisement for public services about the integrated public services 110 that was produced in the form of dialogue (dramatic) with a duration of 4 minutes and 18 seconds in Mp4 format. The results of the analysis concluded that there was a positive influence on the behavior of the people of Batam, especially in the behavior of preventive actions when a crime occurred.